Results Field Trials, Crop 2005: Submitted on behalf of the Analysis Committee of the European Brewery Convention - Didierjean, L. (BrewingScience, 2006)
The present report summarizes the EBC Barley Field Trials for Crop 2005. It is based on the comments of the 4 regional chairmen, and is intended to highlight tested varieties that may be of interest to the malting and brewing industry.